But gluey cyclic utilization express delivery box is exempted from in easy dismouting - GUAN YUNHAO (2017)
The utility model belongs to the technical field of circulated use packing carton, concretely relates to but gluey cyclic utilization express delivery box is exempted from in easy dismouting, the express delivery box body comprises a plurality of box surface that link to each other, is equipped with between the direct box surface who links to each other to make things convenient for folding overlap seam line, and the last side of not connecting box surface of box surface is equipped with connecting device, and the plastic envelope internal fixation of four sides is equipped with the ligature area behind the constitution box body, and the ligature area upwards extends to the box body top surface, and the end in ligature area is equipped with the sealing -in device. This express delivery box stable in structure, easy dismounting does not have nail, no viscose, and green easily retrieves, multiple encryption, ligature are taken to set up and are connected face and plastic film base stock, and it is single conven